2021
DOI: 10.3389/fonc.2021.642571
|View full text |Cite
|
Sign up to set email alerts
|

Breast-Conserving Therapy Has Better Prognosis for Tumors in the Central and Nipple Portion of Breast Cancer Compared with Mastectomy: A SEER Data-Based Study

Abstract: Background and ObjectivesCurrently, the location of primary tumor was an independent prognostic factor of breast cancer. Tumors in the central and nipple portion (TCNP) had poor prognosis compared to other peripheral quadrants. The breast-conserving therapy (BCT) is becoming increasingly common worldwide in breast cancer operations. However, whether the availability of BCT was performed for TCNP remained a matter of debate. We sought to investigate whether BCT was suitable for TCNP with respect to survival out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…[31][32][33] Despite this, BCS at the central tumor location not only does not worsen but also significantly improves the oncological results of treatment in comparison with mastectomy, while achieving the same results as BCS in cases with other tumor locations. [34][35][36][37][38] Current clinical practice considers BCS as a safe option for central tumors, which is consistent with our experience. However, reconstruction of the central part of the breast can be technically challenging.…”
Section: Discussionsupporting
confidence: 89%
“…[31][32][33] Despite this, BCS at the central tumor location not only does not worsen but also significantly improves the oncological results of treatment in comparison with mastectomy, while achieving the same results as BCS in cases with other tumor locations. [34][35][36][37][38] Current clinical practice considers BCS as a safe option for central tumors, which is consistent with our experience. However, reconstruction of the central part of the breast can be technically challenging.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, BCT had a higher overall survival rate than mastectomy for breast cancer in a propensity score matching study based on the SEER database by Wrubel et al. ( 28 ). However, most of these studies included invasive ductal breast cancer (IDC) patients.…”
Section: Discussionmentioning
confidence: 95%
“…In 2016, Marissa et al (16) controversially reported that BCT improved 10-year OS compared with mastectomy after hierarchical analysis of disease stages and adjustment of confounding variables. Similarly, BCT had a higher overall survival rate than mastectomy for breast cancer in a propensity score matching study based on the SEER database by Wrubel et al (28). However, most of these studies included invasive ductal breast cancer (IDC) patients.…”
Section: Discussionmentioning
confidence: 99%
“…So in our study, T3–4 patients were included. Wang's study compared the safety of BCT versus mastectomy for CLBC [ 22 ]. But in our study, non-breast conserving patients included not only mastectomy, but also breast reconstruction.…”
Section: Discussionmentioning
confidence: 99%